EFFECTIVE STRATEGIES FOR DEVELOPING ENGLISH LANGUAGE SKILLS IN ELEMENTARY SCHOOL STUDENTS - Nabila Cahyani; Noviana Barus; Natachya S.W Simamora; Eva Betty Simanjuntak; Muhammad Huzein Zamora Tanjung (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to describe the English proficiency level of upper-grade students at SD Terpadu Muhammadiyah 36 Medan and formulate learning strategies relevant to their linguistic development needs. The research used a descriptive qualitative approach with data collection techniques including interviews and documentation. The results show that the students' proficiency is still at an elementary level, with the main problems being vocabulary mastery, pronunciation accuracy, and understanding of simple sentence structures. The identified inhibiting factors include low exposure to language in the family environment and minimal parental support for learning activities. Based on these findings, innovative learning strategies were formulated through the application of the Total Physical Response (TPR) method, the use of simple digital media, the simplification of linguistic input, and the strengthening of learning motivation through positive reinforcement techniques. The implementation of these strategies is projected to improve the quality of learning interactions, student participation, and English language competency achievement at the elementary school level.